ANALISIS PENDAPATAN USAHA PERIKANAN TANGKAP DAN FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENYALURAN DAN PENERIMAAN KREDIT PERIKANAN DI KECAMATAN AMPANA KOTA - Dewi Nurasih; Alimudin Laapo (Universitas Tadulako, 2009)
The study was done at fishery catching area in Ampana Kota district on April to September 2009. This study was aimed to observe the income level of fishery households and social economics factors that influence delivery and receiving of fishery credit at Ampana Kota district. The research used a survey method. The research results showed that the income level of fishery catching was IDR 8,192,450 per household per year. Credit aid programs can be used as a mean to improve the contribution of fishery sector. The credit delivery and receiving were influenced by age, education level, production and household income.